1994
DOI: 10.1128/aem.60.7.2272-2277.1994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of distance from the polluting focus on relative concentrations of Bacteroides fragilis phages and coliphages in mussels

Abstract: Concentrations of fecal bacteria, somatic and F-specific coliphages, and phages infecting Bacteroidesfragilis in naturally occurring black mussels (Mytilus edulis) were determined. Mussels were collected over a 7-month period at four sampling sites with different levels of fecal pollution. Concentrations of both fecal bacteria and bacteriophages in mussel meat paralleled the concentration of fecal bacteria in the overlying waters. Mussels bioaccumulated efficiently, although with different efficiencies, all of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The use of bacteriophages as new indicators has been suggested (IAWPRC Study Group on Health Related Water Microbiology 1991). The aim of the present research was to evaluate the incidence of enteric viruses in mussels and to verify the possibility of using the somatic coliphage, F-specific coliphages (F-Plus) (Havelaar and Hogeboom 1984) and B40-8 bacteriophages infecting Bacteroides fragilis (Tartera & Jofre 1987;Jofre et al 1994;Lucena et al 1994) as indirect indicators of mussel viral contamination.…”
Section: Introductionmentioning
confidence: 99%
“…The use of bacteriophages as new indicators has been suggested (IAWPRC Study Group on Health Related Water Microbiology 1991). The aim of the present research was to evaluate the incidence of enteric viruses in mussels and to verify the possibility of using the somatic coliphage, F-specific coliphages (F-Plus) (Havelaar and Hogeboom 1984) and B40-8 bacteriophages infecting Bacteroides fragilis (Tartera & Jofre 1987;Jofre et al 1994;Lucena et al 1994) as indirect indicators of mussel viral contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Phages (viruses which infect bacteria) are considered to be better predictors of human enteric virus removal than FIB because of similarities such as composition, morphology, structure, size and site of replication (Jofre et al, 1986;Gantzer et al, 1998;Grabow, 2001;Sinton et al, 2002;Diston et al, 2012;Edbon et al, 2012;Jofre et al, 2014). Consequently, phages, which can be detected using relatively simple, affordable standardized laboratory techniques, have increasingly been used in a variety of different capacities for assessing wastewater treatment and disinfection processes (Tartera and Jofre, 1987;Tartera et al, 1989;Lucena et al, 1994;Grabow, 2001;Purnell et al, 2015. According to Amarasiri et al (2017) phages have been the most widely used microbial parameter for performance validation and operational monitoring with respect to virus reduction efficiency in wastewater treatment processes.…”
Section: Bacteriophages (Phages)mentioning
confidence: 99%
“…Values of the product of the densities of somatic coliphages and their potential hosts reported for the rest of naturally occurring matrixes such as depurated waters (Nieuwstad et al 1988;Grabow et al 1993;Campos et al 2002;Skraber et al 2002;Lucena et al 2004;Mandilara et al 2006) receiving water bodies such as rivers and seas (Wentsel et al 1982;O'Keefe and Green 1989;Cornax et al 1991;Moriñigo et al 1992;Payment and Franco 1993;Contreras-Coll et al 2002;Duran et al 2002;Lucena et al 2003;Skraber et al 2004) groundwater (Abbaszadegan et al 1998;Lucena et al 2006), drinking water (El-Abagy et al 1988Ratto et al 1989;Jofre et al 1995;Mendez et al 2004), cow slurries (Heinonen-Tanski et al 2005), treated sludges such as compost (Guzman et al 2007), polluted marine sediment (Jofre et al 1989), shellfish (Lucena et al 1994;Legnani et al 1998) and other foods (Kennedy and Bitton 1987;Hirotani et al 2002;Hsu et al 2002) are well underneath the 'joint replication thresholds' reported in Table 1. No products of densities of somatic coliphages and their potential hosts reported for the more contaminated of these matrixes reach 10 8 .…”
Section: Naturally Occurring Densities Of Potential Hosts and Somaticmentioning
confidence: 99%